Sikahyflex-Epoxy Mixed Adhesive’s Effect on the Aluminum-Composite Joint’s Shear Tensile Strength for the Automotive Industry - Sri Hastuti; Paryanto Paryanto; Gito Sugiyanto; Xander Salahudin; Ridwan Afandi; Fadlan Azhari (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2024)
The automotive industry sector encounters challenges in the construction of connections between different materials. Hence, a breakthrough is needed in the automotive industry in manufacturing connections between different wall panel materials. Mixed adhesive materials for different materials are required and represent an innovation in the manufacturing process for joints of different materials due to the need for stiff and slightly ductile adhesives. This research aims to analyze the effect of using a sikahyflex-epoxy mixture adhesive in aluminum-composite joints on the shear tensile strength of the joints for the automotive industry. This research serves as an innovation in dissimilar material connection systems by developing the use of mixed adhesives and cocofiber aluminum-composite adherend materials with environmentally friendly and corrosion-resistant properties. The research material used aluminum 5083-cocofiber composite. The adherend surface was roughened employing sandpaper of #60, #80, and #150. The adhesive used the addition of sikahyflex adhesive to the epoxy adhesive with additional variations of 10%, 20%, 30%, and 40% sikahyflex. Connections between different materials with the single lap joint type refer to ASTM D1002. The roughness test results yielded the best roughness grade #150 on the surface of the aluminum adherend and coco fiber composite. The shear tensile test results by adding 40% sikahyflex adhesive, 0.4 mm adhesive thickness, and #150 sandpapering resulted in a 20% increase in shear tensile strength in the single lap joint of 2.51 N/mm2. The surface roughness enhanced the adhesive bond strength between mechanical interlocking adhesives and adherend. Meanwhile, the failure modes observed in macro observations included thin-layer cohesive failure, cohesive failure, two-stage failure, and stock-break failure modes. The SEM observation revealed that in the initial propagation of microcracking and voids, which mark the initial onset of adhesive failure, tearing took place, leading to a failure mode in the aluminum-composite coco fiber single overlap joint.